Thanato - ethics, a necessary discipline for times of death - Farfán Zamalloa, Percy (2020)
Death accompanies life from the very moment of conception. This finite character of the human being has led people to wonder about whether death has value or not, and what are the implications of this question for their existence. From time immemorial, philosophy has reflected on the meaning of death; Bioethics has done the same over time. However, now the reflection on the meaning of death can be accomplished in light of a relatively new discipline, called Thanato-Ethics. Hence, this article explores, through this new discipline, the question of what the meaning of death is. Since death is a very complex reality, we had to take into consideration theoretic fields of knowledge -philosophy and the ethics of death- and practical knowledge -such as an analysis of the dimensions that surround the concrete act of dying. Later, we analyze the implication of euthanasia and assisted suicide. Finally, we conclude recognizing the importance and relevance of this discipline today.